2016
DOI: 10.1038/srep20189
|View full text |Cite
|
Sign up to set email alerts
|

BKM-120 (Buparlisib): A Phosphatidyl-Inositol-3 Kinase Inhibitor with Anti-Invasive Properties in Glioblastoma

Abstract: Glioblastoma is an aggressive, invasive tumor of the central nervous system (CNS). There is a widely acknowledged need for anti-invasive therapeutics to limit glioblastoma invasion. BKM-120 is a CNS-penetrant pan-class I phosphatidyl-inositol-3 kinase (PI3K) inhibitor in clinical trials for solid tumors, including glioblastoma. We observed that BKM-120 has potent anti-invasive effects in glioblastoma cell lines and patient-derived glioma cells in vitro. These anti-migratory effects were clearly distinguishable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 30 publications
4
49
0
Order By: Relevance
“…Furthermore, it inhibits the growth of human tumors in xenograft mouse models in a well-tolerated manner and very efficiently penetrates the blood-brain barrier (8)(9)(10). Buparlisib reduced glioblastoma tumor spread in orthotopic xenograft models (11). A phase I clinical trial using buparlisib on a variety of solid tumors showed good disease control and tolerable toxicity (12 (14).…”
Section: Pi3k Inhibition In Melanoma Brain Metastasesmentioning
confidence: 99%
“…Furthermore, it inhibits the growth of human tumors in xenograft mouse models in a well-tolerated manner and very efficiently penetrates the blood-brain barrier (8)(9)(10). Buparlisib reduced glioblastoma tumor spread in orthotopic xenograft models (11). A phase I clinical trial using buparlisib on a variety of solid tumors showed good disease control and tolerable toxicity (12 (14).…”
Section: Pi3k Inhibition In Melanoma Brain Metastasesmentioning
confidence: 99%
“…In this type of cancer, PI3K mutations are mutually exclusive of PTEN mutations/deletions with 59% of GBM showing one or the other (TCGA GBM Analysis Working Group). The role of phosphatidylinositol 3,4,5-trisphosphate (PI (3,4,5)P3, the product of class I PI3K) is fundamental in cancer research and often considered as 'oncogenic' but other phosphoinositides (PIs) such as phosphatidylinositol 3,4-bisphosphate (PI(3,4)P2) and phosphatidylinositol 4,5-bisphosphate (PI(4,5)P2) are also critical signal molecules particularly in the control of cell adhesion, migration and invasion [3]. These aspects are particularly important in GBM as this type of tumor is well known for its high migratory and invasive potential.…”
Section: Introductionmentioning
confidence: 99%
“…PI (3,4,5)P3 and PI(4,5)P2 are both recognized by members of the inositol polyphosphate 5-phosphatase family, that is, SYNJ2, OCRL, SHIP1/2, INPP5K, INPP5J [3]. Evidence in databases is provided of a significant correlation between increased INPP5K (SKIP) mRNA expression in GBM and improved long-term survival [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations